2017
DOI: 10.1371/journal.pone.0176172
|View full text |Cite
|
Sign up to set email alerts
|

Tracking disease progression by searching paths in a temporal network of biological processes

Abstract: Metabolic disorders such as obesity and diabetes are diseases which develop gradually over time through the perturbations of biological processes. These perturbed biological processes usually work in an interdependent way. Systematic experiments tracking disease progression at gene level are usually conducted through a temporal microarray data. There is a need for developing methods to analyze such highly complex data to capture disease progression at the molecular level. In the present study, we have consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Briefly, out of total ~ 29,411 genes measured, data was processed to filter out genes not perturbed 2 fold even in one time point resulting in a matrix of 19,303 genes across 10 time points. Further details of the processing are given in [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, out of total ~ 29,411 genes measured, data was processed to filter out genes not perturbed 2 fold even in one time point resulting in a matrix of 19,303 genes across 10 time points. Further details of the processing are given in [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…We recently published a similar work [ 9 ] tracking disease progression where the biological processes perturbed at each time point were found and connected using a network of connected biological processes The work analyses progression of data by finding processes perturbed temporally and connecting them resulting in paths, giving proteins of processes of the paths as gene/protein targets. A more precise assessment of importance could be firstly quantitatively defining progression and then quantifying the effect of removal of the protein from the network on progression, which was missing in the previous work [ 9 ]. Here, we address this limitation by making a novel algorithm giving a more detailed quantitative assessment of the importance of the protein in question.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at understanding the pathogenesis of heart disease based on time course RNA-seq dataset, Ma et al proposed the inference of multiple differential modules (iMDM) algorithm to identify gene modules across multiple differential coexpression networks [8]. Based on temporal microarray data of gene expression, Rajat et al obtained dysregulated gene modules at 10 time points, which constitute paths of the disease evolution [9]. Srihari et al identified cancer-related protein complexes via analyzing expression level differences for normal and cancer conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Graphs are used to study many real-world problems such as information propagation in social networks [6,23], spreading of epidemics [3,30], protein interactions [1,31], activity in brain networks [12,15], and more. Over the years the graph models are enriched with information of node and edge attributes and edge timestamps, giving rise to attributed graphs [29,35] and temporal graphs [22,28], which are used to capture complex phenomena and network dynamics.…”
Section: Introductionmentioning
confidence: 99%